Bio-Based Smart Materials for Food Packaging and Sensors – A Review - Halonen, Niina; Pálvölgyi, Petra S.; Bassani, Andrea; Fiorentini, Cecilia; Nair, Rakesh; Spigno, Giorgia; Kordas, Krisztian (Frontiers in Materials, 2020)
Food industry must guarantee food safety and seek sustainable solutions for increasing shelf life and decreasing food waste. Bio-based smart packaging is a potential option, where sustainability and real-time monitoring of food quality are combined assuring health safety and providing economic and environmental benefits. In this context, bio-based refers not only to packaging materials that are from renewable sources and biodegradable, but also to the sensor elements. The scope of this review is to explore the state-of-the-art of bio-based polymers used as food contact materials and to highlight the potential of natural compounds for sensing chemical and physical changes of the environment to monitor the food quality. Finally, different sustainability aspects of the bio-based materials are discussed.